Technocentrism, Disembodied Relationship, and Sabbath - Papula, Marissa (Lumen et Vita, 2015)
As developments in technology present us with new opportunities for efficiency and connection, digital communication and our growing dependence on the internet are increasingly blurring boundaries between work and rest, between “real life” and the “lives” we share on social media platforms. Our text messages substitute for time together. Our best news is shared via email or in photos posted for all to see, rather than embraces and champagne toasts. Our deepest secrets are poured anonymously onto the Internet for others’ consumption. We text, email, scroll, and post our way through meetings, meals and milestones, multitasking, somehow creating more time and yet realizing our opportunities for refreshment and authentic relationship are shrinking as our expectations for productivity are ever expanding. We are privy to the life events of our high school teammates, but are unable to verbalize our suffering in the presence of another, face to face, sans a keyboard. My writings critique this growing phenomena through a lens of theological anthropology. Our technocentrism is deeply contouring how we live, how we relate to one another, and how we engage in work and leisure, and prompts us to ponder what our dependence on technology means for us as human beings. Through a theological exploration of human relationship and Sabbath, I will explore how technocentrism is thwarting our theosis, both individually and societally, and offer suggestions for how we can best appropriate technological advances in communication toward better bearing the image of God in our familial, social, and professional lives.